(3GdUMGM aj GddZIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3YeQh Hf SdjeGf GdNhdGfi s)
(3ChdgG (B:s
(3HGH GdQGA , aUd GdCda (B: (3CHQ , GdCHQI hGMOI GdEHQ s
(3BNQgG (B:s
(3aUd GdjGA , jbX QLd hjbX Je GdLRA GdKGfi ef cJGH GdUMGM hjJdhg GdLRA GdKGdK Ef TGA Gddg HGH GdUGO s
(3GdfSNI eYGQVI Ydi CUdg GdPi fbd efg (B664(3g`s
(3hcJHJ HYV GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
Keywords: (3GddZIs